Re-Engineering the Human Resource Strategies Amid and Post-Pandemic Crisis: Probing into the Moderated Mediation Model of the High-Performance Work Practices and Employee's Outcomes - Zhiqiang, Ma; Khan, Hira Salah ud din; Chughtai, Muhammad Salman; Mingxing, Li (Frontiers in Psychology, 2021)
By incorporating the conservation of resource theory, this study examines how high-performance work practices (HPWPs) affect the employee's in-role performance (EIRP) and employee's task performance (ETP) during the coronavirus disease 2019 (COVID-19) pandemic. Furthermore, this study investigates how organization-based self-esteem (OBSE) and positive psychological capital (PPC) affect the relationship between HPWPs and outcomes of employees such as EIRP and ETP. A quantitative technique based on the survey method was used to gather the primary data of the investigation. Two hundred and eleven bank employees working in different banks of Punjab and Pakistan participated in the survey process. The PROCESS-macro was used to test the relationship among the study constructs. Our results supported all the study hypotheses, however positive psychological capital did not moderate the indirect effect of high performance work practices on employee's task performance via organization based self-esteem. This study is the earliest of its kind that focuses on HPWPs and outcomes of employees amid the COVID-19 pandemic in a developing country like Pakistan. The findings of this study provide practical implications in the post and continuing pandemic situation for organizations to human resource management to redesign workforce strategies to increase their contribution and responses to realize organizational priorities. Although researchers have explored the topic in different sectors, scant studies have investigated the potential impact, barriers, and enabling mechanisms that function as a catalyst in HPWPs during the pandemic situation.